Revealing How to Analyze Public Purchase Intentions Toward Green Products in Emerging Markets in the Jakarta Region - Vionyka Amanda Erditia; Debbie Aryani Tribudhi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study investigates the effects of environmental concern, green attitude, subjective norms, and perceived behavioral control on the intention to purchase green products, with environmental knowledge as a moderating variable. Using survey data from 190 Indonesian participants, the findings indicate that environmental concern positively shapes green attitude, subjective norms, and perceived control. Subjective norms also contribute significantly to both perceived control and green purchase intention. However, green attitude and perceived control do not directly influence intention. Environmental knowledge enhances the relationship between attitude and intention. The confirmed hypotheses support the overall model framework.